A method for preserving fungal culture - Saad, Wan Zuhainis; Sieo, Chin Chin; Ahmad, Syahida; Abdullah, Norhani; Al-Bajalany, Laith Yaseen Arif (2014)
The present invention relates to a method for preserving fungal culture. The method comprises of providing a fungal culture; placing the fungal culture on a first slide and cover the first slide with a second slide; pressing the slides to form a pressed fungal culture and separating the slides to expose the pressed fungal culture; dropping a mixture of mineral oil and potato dextrose broth to the pressed fungal culture and place the second slide onto the first slide; incubating the pressed fungal culture; cutting the fungal culture into plurality of segment; removing a segment of the fungal culture and place it onto an agar; incubating the segment of the fungal culture; putting the incubated fungal culture into a cryovial; adding mineral oil to the fungal culture in the cryovial; incubating the fungal culture in the cryovial; putting the cryovial containing the fungal culture into a preservative mixture; and freezing the fungal culture.